Implementasi Pengiriman Data Sensor LM35 untuk Perbandingan Waktu Insert pada Basis Data MySQL dan MongoDB - Rangga Noviansyah Nuur Aziiz; Mochammad Hannats Hanafi Ichsan; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
At this moment, there are so many data transfer among the system of computation. And with the term of internet of things where many relations which create a network consist of man to machine relation as well as machine to machine. Also the transferred data are various. Started with numeric data up to character data. And there is sensoric data which began to develop on usage of internet of things such as smarthome. With this many variety of data, create some issues of needs which one of them is a container of data or could be called database. In this research, the compared database are MySQL database and MongoDB database to compares which type of database is better to send sensoric data into the database. There are hardwares which are used for implementing the scenario are Arduino Uno Microcontrollerboard and LM35 IC. And there are softwares to support this research such as PHP programming language. The test of the system will be started with sending sensor data into 1 table, 2 table, and 3 table to each of database with 10 times data transfer so that we obtain the execution time of insert query as a compared parameter of database.